Social Responsibility and Corporate Governance of Islamic Banks - Mathkur, Naif Mansour M. (Archives of Business Research, 2019)
The goal of this research undertaking is to provide the perspicacious insights on corporate social responsibility and Shari’ah governance activities of Islamic banks. This research offers illuminations on how Islamic banks can improve their corporate social responsibility and Shari’ah governance endeavors. For this, the study adopts a comprehensive and fastidious literature review that covers an array of primary, secondary, and tertiary sources. The study finds that the Social responsibility and Shari’ah corporate governance practices of Islamic banks are combinations of obligatory and recommended programs. Most Islamic banks do not adequately meet the expectations placed upon them by adherents of the Islamic faith in matters of social disclosure and scope of corporate social responsibility activities. The Islamic banking industry has come a long way in issues of corporate governance. However, Islamic banks need to be at the forefront of pioneering innovative, impactful, and far-reaching social responsibility and corporate governance practices since for starters, they are faith-based institutions. Islamic banks need to stop resting on their laurels and stop playing catch up in these domains. Moreover, Islamic banks need to deal conclusively with the array of challenges facing their Shari’ah corporate governance endeavors so as to meet their objectives in a more effective manner. This paper is exploratory in nature. There is a need for further empirical investigation.